Modelo Numérico De Agua Subterránea En El Abanico Aluvial De Yopal Como Herramienta Para Realizar Una Correcta Gestión Del Recurso Hídrico - Cuta García, Sulma Milena (Universidad Antonio Nariño, 2023)
Population growth and the collapse of the Potable Water Treatment Plant since 2011 in the municipality of Yopal has caused the main source of supply to be groundwater, through the exploitation of aquifers through wells, cisterns and springs. significantly increasing the demand for different uses such as agriculture, livestock, industry and mainly human consumption, given the problem of water scarcity and the need to carry out adequate management of underground water resources.